Análisis crítico-jurídico sobre los factores que inciden en el alistamiento de menores en bandas delictivas del Ecuador. - Hidalgo Heredia, Cristian Iván (2024)
The article addressed the problem of the recruitment of minors into criminal gangs in Ecuador, a phenomenon that has raised growing concern due to its impact on social security and well-being. The objective was to carry out a critical-legal analysis, based on Ecuadorian legal regulations and the international context, to determine the factors that influence the enlistment of minors in criminal gangs in Ecuador. A qualitative modality was used, with a non-experimental design and a cross-sectional study, as well as a legal-descriptive scope. The results obtained through semi-structured interviews with key informants, such as lawyers and judges, revealed that economic precariousness, family disintegration, and the legal vulnerability of minors were key factors that facilitated their recruitment by criminal gangs. Likewise, it was also noted that deficiencies in the application of current legal regulations contributed to the expansion of this phenomenon, since the gangs took advantage of legal gaps and the lack of institutional control. This study concluded that it is essential to implement legal reforms and strengthen preventive and socio-educational measures to reduce the vulnerability of minors and limit their participation in criminal activities, thus contributing to improving security and well-being in the affected communities.